Does Adipose Tissue Thermogenesis Play a Role in Metabolic Health? - Craig Porter; Elisabet Børsheim; Labros S. Sidossis (Journal of Obesity)
The function ascribed to brown adipose tissue in humans has long been confined to thermoregulation in neonates, where this thermogenic capacity was thought lost with maturation. Recently, brown adipose tissue depots have been identified in adult humans. The significant oxidative capacity of brown adipocytes and the ability of their mitochondria to respire independently of ATP production, has led to renewed interest in the role that these adipocytes play in human energy metabolism. In our view, there is a need for robust physiological studies determining the relationship between molecular signatures of brown adipose tissue, adipose tissue mitochondrial function, and whole body energy metabolism, in order to elucidate the significance of thermogenic adipose tissue in humans. Until such information is available, the role of thermogenic adipose tissue in human metabolism and the potential that these adipocytes may prevent or treat obesity and metabolic diseases in humans will remain unknown. In this article, we summarize the recent literature pertaining to brown adipose tissue function with the aims of drawing the readers’ attention to the lack of data concerning the role of brown adipocytes in human physiology, and to the potential limitations of current research strategies.